Evaluation of velocity and acceleration effect on mecanum wheel robot positioning - Bączyk, Aleksander; Wojtowicz, Przemysław; Klekiel, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a Mecanum wheel omnidirectional robotic platform made for taking measurements in harsh and dangerous conditions is introduced. Due to the necessity of highly accurate displacement of the platform for measuring the conditions at the exact measurement point and due to known Mecanum wheel slippage and relatively poor position accuracy, a calibration procedure for minimizing positioning error had to be implemented.
Keywords: robot; Mecanum wheel; calibration; optical measurements